UV‐Inert ZnTiO3 Electron Selective Layer for Photostable Perovskite Solar Cells. Issue 40 (18th September 2019) - Wei, Jing; Guo, Fengwan; Liu, Bing; Sun, Xiangyu; Wang, Xi; Yang, Zijiang; Xu, Kun; Lei, Ming; Zhao, Yicheng; Xu, Dongsheng
Abstract: Although planar‐structured perovskite solar cells (PSCs) have power conversion efficiencies exceeding 24%, the poor photostability, especially with ultraviolet irradiance (UV) severely limits commercial application. The most commonly‐used TiO2 electron selective layer has a strong photocatalytic effect on perovskite/TiO2 interface when TiO2 is excited by UV light. Here a UV‐inert ZnTiO3 is reported as the electron selective layer in planar PSCs. ZnTiO3 is a perovskite‐structured semiconductor with excellent chemical stability and poor photocatalysis. Solar cells are fabricated with a structure of indium doped tin oxide (ITO)/ZnTiO3 /Cs0.05 FA0.81 MA0.14 PbI2.55 Br0.45 /Sprio‐MeOTAD/Au. The champion device exhibits a stabilized power conversion efficiency of 19.8% with improved photostability. The device holds 90% of its initial efficiency after 100 h of UV soaking (365 nm, 8 mW cm −2 ), compared with 55% for TiO2 ‐based devices. This work provides a new class of electron selective materials with excellent UV stability in perovskite solar cell applications. Abstract : A UV‐inert ZnTiO3 is demonstrated to be an electron selective layer in perovskite solar cells. ZnTiO3 is a perovskite‐structured semiconductor with excellent chemical stability and poor photocatalysis. Planar perovskite solar cells based on ZnTiO3 exhibit power conversion efficiency of 20.1% with improved photostability. The best device holds 90% of its initial efficiency after 100 h of ultraviolet soaking.